Optimization Of Wastewater Treatment Installations In The Palm Oil Industry - Aster Rahayu; Siti Jamilatun; Irwan Mulyadi (Program Studi Teknik Kimia, Universitas Pamulang, 2023)
The liquid waste generated from the palm oil mill can pollute the environment due to the oils it produces, before being discharged into the environment it is necessary to treat the waste so it does not pollute the surrounding environment. Treatment of wastewater using coagulants will greatly affect the quality of wastewater. This study aims to process wastewater so that it can be disposed of the environment without contaminating the environment, besides that this study aims to compare and find out what types of coagulants are good for handling wastewater, while the coagulants used are Tawas, PAC, Alum Polymer and PAC Polymers. The method used to measure total suspended solids (TSS) is the gravimetric method so that the highest total suspended solids results are obtained using a PAC coagulant, namely 1227 with the lowest average efficiency value of 60.66%.